In-situ measurements of stress during thermal shock in clad pressure vessel steel using synchrotron X-ray diffraction. (15th February 2021) - Oliver, Sam; Simpson, Chris; Collins, David M.; Reinhard, Christina; Pavier, Martyn; Mostafavi, Mahmoud
Highlights: Synchrotron X-ray diffraction was used to measure the transient strain in the material during a thermal shock event on cladded steels. Stress intensity factor was deduced which showed its maximum occurring less than a second after the thermal shock event. Despite detailed calibration of the simulations, the experiment and simulation did not match fully. Further calibration could have been done to match the experiment and finite element, but this is contrary to industrial practice. This demonstrates the need for detailed experiments. Abstract: Thermal shocks are an important incident in operation of a pressure vessel which can have a significant impact on the structural integrity of the vessel. Often experiments that consider the state of the vessel before and after the thermal shock are used to evaluate the effects of the thermal shock. The studies can be complemented by time-resolved numerical simulations, which may be validated against the final state of the vessel obtained experimentally, to infer the transient response of the material. The transient response is important as the material experiences the highest level of stress in a short period which can induce catastrophic failure. This paper reports time-resolved experimental quantification of strain in reactor pressure vessel material during thermal shock measured by in-situ synchrotron diffraction. Specimens were extracted from a plate of nuclear pressure vessel steel with a nickel alloy cladding deposited by overlay welding. The specimens, with and without cracks, were subjected to thermal loading by heating then rapidly quenching the cladding in cold water. Strains were measured during thermal loading at a point near the crack tip from which the stress state around the crack tip was calculated and compared with a transient finite element model of the experiment. It was found that the peak near-tip stress occurred within the first second after the onset of rapid cooling. It was demonstrated from experimental measurements that the peak stress intensity factor occurred during thermal shock, rather than under steady conditions before or after the thermal shock. It was shown that although the finite element simulation predicts the steady state condition of the material after thermal shock, its transient response dependents significantly on a number of inputs with high uncertainty, making its time-resolved results unreliable for high-fidelity integrity assessments. Graphical abstract: Image, graphical abstract